2021
DOI: 10.3390/nano11040960
|View full text |Cite
|
Sign up to set email alerts
|

XRD Evaluation of Wurtzite Phase in MBE Grown Self-Catalyzed GaP Nanowires

Abstract: Control and analysis of the crystal phase in semiconductor nanowires are of high importance due to the new possibilities for strain and band gap engineering for advanced nanoelectronic and nanophotonic devices. In this letter, we report the growth of the self-catalyzed GaP nanowires with a high concentration of wurtzite phase by molecular beam epitaxy on Si (111) and investigate their crystallinity. Varying the growth temperature and V/III flux ratio, we obtained wurtzite polytype segments with thicknesses in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
2
5
0
Order By: Relevance
“…This is twice the stoichiometric value for planar GaP layers [29,30] corresponding to the atomic V/III flux ratio (V/III for brevity) of 2. These conditions yield stable ZB GaP NWs as previously reported [26][27][28]. The measured contact angles of Ga droplets on tops of these NWs are 120±5°(not shown), which is close to the previously reported value of 123° [22].…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…This is twice the stoichiometric value for planar GaP layers [29,30] corresponding to the atomic V/III flux ratio (V/III for brevity) of 2. These conditions yield stable ZB GaP NWs as previously reported [26][27][28]. The measured contact angles of Ga droplets on tops of these NWs are 120±5°(not shown), which is close to the previously reported value of 123° [22].…”
Section: Methodssupporting
confidence: 91%
“…The Ga beam equivalent pressure (BEP) was kept constant at 7×10 −8 Torr throughout the growth, which corresponds to 3.17 nm min −1 Ga-limited planar growth rate of GaP. The P 2 flux was different in the two growth steps [28]. In the first step (1 h duration), the P 2 BEP was set at 8.4×10 −7 Torr, yielding a V/III BEP ratio of 12.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, NW growth was interrupted by closing both Ga and P 2 shutters and subsequent sample cooling. An in situ analysis of the NW crystal structure performed with reflection high energy electron diffraction (RHEED) patterns demonstrated that the described growth conditions yielded stable formation of GaP NWs with a zinc-blende structure as it was previously reported in [36][37][38].…”
Section: Gapas/gap Nw Led Array Synthesissupporting
confidence: 62%
“…The details on TEM studies of NW crystal structure are provided in Supplementary Materials . A more detailed investigation of GaP NW crystal structure and its dependence on the growth conditions was performed using X-ray diffraction technique with an in-house X-ray source [ 50 ].…”
Section: Methodsmentioning
confidence: 99%